Modelo de cuidado de enfermagem centrado na família para terapia intensiva neonatal – AMCORE - Kegler, Jaquiele Jaciara (2023)
This study aimed to build a family-centered nursing care model for neonatal intensive care. This is qualitative research, with a participatory approach, developed in three stages. First, there was the elaboration of concepts, assumptions, care methodology and diagram. In the first stage, concepts were elaborated from discussion groups with members of a research group in December 2020 and validated by them in groups held in June 2021. Assumptions were elaborated from the theoretical framework of the thesis and the experience of the authors of this study. The care methodology was elaborated based on other care models, the theoretical framework of the thesis and the practical experience of the doctoral researcher. A diagram was created to graphically represent the constructed model. In the second stage, 15 individual/group interviews were carried out with nurses from a Neonatal Intensive Care Unit of a public hospital in the central region of Rio Grande do Sul, with the aim of assessing the care model built in the previous stage. Data were analyzed using deductive thematic analysis. In the third stage, after assessing the model coherence and convergence, individual/collective semi-structured interviews were carried out with 11 fathers/mothers of newborns hospitalized in the same unit of the previous stage, between June and August 2022. Data were submitted to deductive thematic analysis. The study was approved by a Research Ethics Committee. The constructed model is formed by the concepts of newborn, Neonatal Intensive Care Unit, family, nursing, family-centered care and health-disease, by six assumptions and six phases - acclimatizing, knowing each other, connecting, recognizing the family’s needs and strengths, developing care in partnership with the family and rethinking the process. It was assessed by nurses as easy to understand and with practical applicability. The concepts, assumptions and methodology of care were considered clear, simple, sufficient, complete and consistent with practice. It was also coherent and convergent with the practice from parents’ perspective. The built model can guide family care in Neonatal Intensive Care Units. Moreover, it contributes to the training and permanent education of future professionals by disseminating and facilitating the implementation of precepts of family-centered care in practice as well as with the development of nursing especially with regard to the necessary visibility that theory and practice are inseparable and necessary for quality, humanized and participatory care.